2000
DOI: 10.1046/j.1365-2141.2000.02365.x
|View full text |Cite
|
Sign up to set email alerts
|

Effective lysis of model thrombi by a t-PA mutant (A473S) that is resistant to alpha2-antiplasmin

Abstract: This study used two mutants of tissue-type plasminogen activator (t-PA) with resistance to inhibitors of fibrinolysis to define the contribution of plasminogen activator inhibitor (PAI)-1 and alpha2-antiplasmin (alpha2-AP) to the control of fibrin lysis. Wild-type t-PA was compared with KHRR296-299AAAA, which is resistant to PAI-1, and with A473S, which is resistant to alpha2-AP. We examined these forms of t-PA in model systems that are physiologically relevant. Neutralization of alpha2-AP was essential for ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2001
2001
2005
2005

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 44 publications
2
10
0
Order By: Relevance
“…Clot lysis experiments confirmed that the endogenous thrombolysis potential is significantly enhanced in α2-AP -/-mice, indicating a physiological role of α2-AP in fibrin surveillance [38]. We have previously reported that tPA increases the rate of clot lysis after endothelial injury [34] and other study showed the functional significance of α2-AP as a direct inhibitor of tPA, which explains the basis of the accepted role of α2-AP as a regulator of fibrin persistence and thrombus resistance to lysis [39].…”
Section: Pulmonary Embolismsupporting
confidence: 76%
“…Clot lysis experiments confirmed that the endogenous thrombolysis potential is significantly enhanced in α2-AP -/-mice, indicating a physiological role of α2-AP in fibrin surveillance [38]. We have previously reported that tPA increases the rate of clot lysis after endothelial injury [34] and other study showed the functional significance of α2-AP as a direct inhibitor of tPA, which explains the basis of the accepted role of α2-AP as a regulator of fibrin persistence and thrombus resistance to lysis [39].…”
Section: Pulmonary Embolismsupporting
confidence: 76%
“…Model thrombi formed from whole blood lysed without the addition of proteases. This lysis occurred despite the high concentrations of inhibitors present in these thrombi (Robbie et al, 1997(Robbie et al, , 2000. After the initial observations in model thrombi prepared from whole blood, thrombi prepared from PRP and PMNs were used to allow the cellular contribution to lysis to be analysed more directly.…”
Section: Discussionmentioning
confidence: 99%
“…Thrombi formed in the Chandler loop system contain all these components and have structures similar to human in vivo thrombi (Robbie et al, 1997). The cellular elements are well placed to modify the lytic process, and platelets have already been identified as modifying lysis via their PAI-1 content (Robbie et al, 1993(Robbie et al, , 1997(Robbie et al, , 2000. This system is more appropriate to the study of thrombus lysis than homogeneous fibrin clots prepared from plasma in the absence of cells, which are often used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rates of clot lysis were determined in samples collected 2 h after electrolytic injury using the methods described by Robbie et al (2000). Plasma (100 l) was added to a 96-well plate, followed by the addition of various concentrations of human recombinant tPA and incubated at room temperature for 5 min.…”
Section: Downloaded Frommentioning
confidence: 99%